(untitled) (Asian Journal of Medical and Biological Research, 2022)
Hemato-biochemical parameters aid in the formulation of effective treatment and supportive therapy for infectious diseases of animals such as peste des petits ruminants (PPR). The present study investigated the prevalence of PPR in Black Bengal goats reared in Jaintapur, Sylhet and concurrent hematology, liver and kidney function tests of PPR infected goats. Information of PPR infected goats was recorded according to age and sex by asking questions to the owner or farmers. Blood samples from 10 PPR-infected Black Bengal goats and 10 normal healthy goats were collected and analyzed using routine blood and biochemical tests. PPR positive cases were found in 60 of 125 goats examined based on clinical signs. The highest prevalence (50%) was recorded in young goats (below 12 months) followed by goats of 12-24 months of age and older goats (above 25 months). Older goats were less susceptible to PPR infection. Male goats were less susceptible to PPR infection (31.66%) compared to female goats (68.33%). PPR is more likely in goats with lower body condition score (BCS). PPR-infected goats had macrocytic hypochromic anemia, as evidenced by significantly lower TEC, Hb, and PCV levels and higher MCV and MCH levels. The total leucocyte count (TLC) was significantly (P<0.05) decreased, neutrophils numbers were significantly increased but lymphocyte numbers were decreased in PPR infected goats. ALT, AST and creatinine reflect the liver and kidney functions. PPR-infected goats had significantly higher (P<0.05) AST, ALT and creatinine values than normal healthy goats. A high level of AST and ALT in PPR-infected goats might be due to liver damage. The high creatinine level indicates functional damage to the kidney. In conclusion, Prevalence of PPR in higher in Black Bengal goats reared in Jaintapur, Sylhet and PPR virus altered the hematological parameters and liver and kidney function test of the PPR infected goats. Asian J. Med. Biol. Res. 2022, 8 (4), 270-276